Sources of Information on Medicinal Products Among Physicians – A Survey Conducted Among Primary Care Physicians in Poland - Zielińska, Magdalena; Hermanowski, Tomasz (Frontiers in Pharmacology, 2022)
Introduction: Primary care physicians, as a specialization that requires extensive knowledge, without age, gender, or type of diseases among patients, face special challenges due to the need to have up-to-date knowledge in various fields of medicine. This is one of the reasons why primary care physicians should use high-quality information sources and have credible and up-to-date medical knowledge. There is a lack of information on the use and credibility of sources of information on medicinal products among Polish doctors. The main goal of this study was to analyze the sources of information on medicinal products among primary care physicians in Poland. Methods: A survey was conducted among 316 primary care physicians in Poland. The first part of the survey included questions about the gender and age of the respondents. The next questions concerned the self-assessment of the respondents in relation to their knowledge about medicinal products as well as the type and frequency of using data sources on medicinal products in the last 6 months. In the last part of the questionnaire, information was collected on the causes that hinder access to credible information about medicinal products, the doctors' assessment of the credibility of the sources used and the influence of a given source on the choice of the product prescribed to the patient, as well as the influence of other factors on prescription decisions. Results: The most frequently mentioned sources of information were medical representatives (79%), medical journals (78%) and congresses, conventions, conferences, and training (76%). The greatest difficulty in finding the latest information about medicinal products was the lack of time. The surveyed doctors considered clinical guidelines to be the most credible source of information, and this source also had the greatest impact on the choice of prescribed medicinal products. Conclusions: The study showed that clinicians consider clinical guidelines as the most credible source of information with the greatest impact on prescribing medicinal products. However, it is not the source most often mentioned by doctors for obtaining knowledge about medicinal products. There is a need to develop strategies and tools to provide physicians with credible sources of information.